2013
DOI: 10.5588/ijtld.12.0427
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of nevirapine when given with isoniazid in South African HIV-infected individuals [Short communication]

Abstract: Summary Isoniazid preventive therapy is recommended in patients on antiretroviral therapy. Isoniazid inhibits CYP3A4, which metabolizes nevirapine. Administration of isoniazid may cause higher nevirapine concentrations and toxicity. We studied the effect of isoniazid on nevirapine concentrations in 21 patients randomized to either placebo (n=13) or isoniazid (n=8) in an ongoing trial of IPT in patients on ART. Isoniazid was associated with a 24% increase in median nevirapine AUC0-12, which was not statisticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…It is recommended that INH (and other hepatotoxic drugs) be withheld in case a patient's transaminase exceed 3 times the upper limit of normal level if associated with symptoms or 5 times the upper limit of normal if the patient is asymptomatic [2] [6] [22] [23]. The finding of the case series is consistent with the available literature emphasizing that stopping INH as soon as INH hepatotoxicity is diagnosed improves mortality risk.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…It is recommended that INH (and other hepatotoxic drugs) be withheld in case a patient's transaminase exceed 3 times the upper limit of normal level if associated with symptoms or 5 times the upper limit of normal if the patient is asymptomatic [2] [6] [22] [23]. The finding of the case series is consistent with the available literature emphasizing that stopping INH as soon as INH hepatotoxicity is diagnosed improves mortality risk.…”
Section: Discussionsupporting
confidence: 67%
“…Case 4 remained on HAART holiday for several weeks and liver function tests normalized on the 25 th day after stopping INH. Although, previous findings show that there is no statistically significant association between ARVs (especially Nevirapine) and developing INH associated hepatotoxicity [6] [22], Cases 1 and 4 show a clinical association between Nevirapine and severity of INH hepatotoxicty. It is important to note that the findings from previous studies which showed that the association of Nevirapine and INH hepatitis was not statistically significant were limited by the small number of patients that were studied [13] [19].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Currently available limited data advises that the concurrent administration of isoniazid with nevirapine is relatively safe [12, 13]. In a brief report by Decloedt et al, an evaluation of the pharmacokinetics of nevirapine when given with isoniazid showed that co-administration was associated with a 24% increase in median nevirapine area under the curve within the first 12 h. This result was, however, not statistically significant and the sample size used in this study was too small to establish the effect of slow and fast isoniazid acetylators on nevirapine as it is possible that the inhibiting effect of isoniazid in slow acetylators may be more pronounced [14]. …”
Section: Introductionmentioning
confidence: 82%
“…However, food intake is known to decrease the bioavailability of INH (24), and we were unable to evaluate pharmacokinetics in the absence of feeding. Concomitant medicines frequently used in LBW infants included theophylline and NVP, neither of which should impact the pharmacokinetic parameters of INH (25,26).…”
Section: Discussionmentioning
confidence: 99%